Gender differences in patients presenting with non-ST elevation acute coronary syndromes - Kalatsei, Liudmila; Yahathugoda, Dilmi R.; Rodrigo, Payagala W. D. A. D. M.; Lenagala, Tahani A. (International Journal of Research in Medical Sciences, 2026)
Background: Although a role for gender-based differences in the development and associated complications of non-ST elevation acute coronary syndromes (NSTE-ACS) has been theorized, there is currently high uncertainty on the actual contribution of these factors in the epidemiology and clinical course of NSTE-ACS. Methods: The retrospective study included 96 patients with NSTE-ASC, who were admitted to the Grodno Regional Clinical Cardiological Center (Belarus) for treatment over a period from January to Оctober 2025. Patients were divided into 2 groups according to their gender: group 1 included 49 male patients, while group 2 – included 47 female patients. All patients underwent clinical, laboratory, and instrumental studies. Statistical analysis was performed using STATISTICA 12.0. Results: Female patients were significantly older (p=0.005); and more often had obesity (p=0.02). Female patients were significantly more diagnosed with unstable angina (p<0.001), while in male patients myocardial infarction (MI) diagnosis was more common. High-sensitive troponin I levels were comparable between two groups (p=0.12), as well as lactate dehydrogenase (p=0.09) and creatine phosphokinase MB (p=0.98). The results of coronary angiography show a tendency towards more extensive multivessel coronary artery disease in men (35% versus 17%, p=0.048). Conclusions: These findings emphasize the importance of gender-specific approaches to the diagnosis and risk stratification of ACS. Larger, multicentre prospective studies incorporating additional biomarkers and long-term outcome data are needed to validate these results and to advance a more balanced approach to the gender-specific management of ACS.